Clinical significance of lower-lobe interstitial lung disease on high-resolution computed tomography in patients with idiopathic pleuroparenchymal fibroelastosis. (July 2019) - Kono, Masato; Fujita, Yuiko; Takeda, Kenichiro; Miyashita, Koichi; Tsutsumi, Akari; Kobayashi, Takeshi; Miki, Yoshihiro; Hashimoto, Dai; Enomoto, Noriyuki; Nakamura, Yutaro; Suda, Takafumi; Nakamura, Hidenori
Abstract: Background: Idiopathic pleuroparenchymal fibroelastosis (IPPFE) is a rare form of idiopathic interstitial pneumonias (IIP) and may have other patterns of interstitial lung disease (ILD) in the lower lobe, such as usual interstitial pneumonia (UIP). However, the clinical significance of lower-lobe ILD in patients with IPPFE is unclear. Methods: A retrospective review of 40 consecutive patients with clinically diagnosed IPPFE in our institution from 2005 to 2016 was conducted. The presence of lower-lobe ILD on high-resolution computed tomography (HRCT) was assessed and classified into UIP or non-UIP pattern according to a modification of diagnostic criteria for idiopathic pulmonary fibrosis. Clinical characteristics and prognostic factors were evaluated. Results: Among the 40 patients with IPPFE, 21 (53%) had lower-lobe ILD, including 13 with UIP pattern and 8 with non-UIP pattern. Patients with IPPFE who had lower-lobe ILD had significantly older age, higher frequency of fine crackles, higher serum KL-6 level, lower residual volume (RV), and lower total lung capacity (TLC) than those without lower-lobe ILD. In addition, those with lower-lobe ILD, especially UIP pattern, had a significantly poorer survival than those without lower-lobe ILD (log-rank test; p = 0.014, p < 0.001, respectively). Multivariate Cox proportional hazards regression analysis revealed that low %forced vital capacity (%FVC) at baseline and coexistence of UIP pattern were significantly associated with poor prognosis in patients with IPPFE. Conclusions: The coexistence of lower-lobe ILD on HRCT, especially the UIP pattern, may predict poor survival in patients with IPPFE. Highlights: In 40 patients with IPPFE, 21 had lower-lobe ILD, including 13 with UIP pattern. IPPFE with lower-lobe ILD had a significantly poorer survival than those without it. Low %FVC and coexistence of UIP pattern were poor prognostic factors in IPPFE. Abstract : This study demonstrated that patients clinically diagnosed with idiopathic pleuroparenchymal fibroelastosis (IPPFE) often have characteristic findings of lower-lobe interstitial lung disease (ILD) on high-resolution computed tomography (HRCT), predominantly of usual interstitial pneumonia (UIP) pattern. The coexistence of lower-lobe ILD, particularly UIP, was an independent poor prognostic factor in these patients.